PERANAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK DESA CIBAHAYU TASIKMALAYA - Zaenuri, Zaenuri; Azizah, Lula (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
The study aims to know the role and efforts of parents in buildingthe character of children, as well as the theory of character formation ofchildren. This research is a qualitative descriptive study. Data collectiontechniques used are in-depth interviews, observation, and documentation.Data analysis technique used is interactive model analysis using threemain components, namely data reduction, data presentation, andconclusion. To obtain data with a high degree of validity used datatriangulation method with the source. The results of this study is that therole of parents is fully implemented properly, but there are still parentswho snarled and scolded children when not following the parent's orders,while for the formation of the child's own character is still not goodbecause it is still influenced by internal factors and extern is the personalself-desire of children who do not want to change as well as the socialenvironment and the less educational spectacle.